1997
DOI: 10.1063/1.119024
|View full text |Cite
|
Sign up to set email alerts
|

Low threshold InGaAlAs monolithic vertical cavity bistable device at 1.5 μm wavelength

Abstract: A monolithic vertical cavity bistable device based on the InGaAlAs system has been grown by low pressure metalorganic vapor phase epitaxy in a single run. First observation of all-optical bistability is reported in this new monolithic structure, with a contrast of 15:1 and a threshold power of less than 300 μW. X-ray diffraction and reflectivity measurements confirmed the high crystallographic and optical qualities of the material. This result shows that the InGaAlAs system is well suited to the fabrication of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

1998
1998
2006
2006

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…(Al)GaInAs has attracted much attention due to properties which make Lt useful for applications to optoelectronic structures such as vertical-cavity surface-emitting lasers (VCSEI) [1,2]. Distributed Bragg mirror structures prepared with this material system for 1.3-1.5 µm wavelength VCSEL devices are generally developed on InP substrates [3].…”
Section: Introductionmentioning
confidence: 99%
“…(Al)GaInAs has attracted much attention due to properties which make Lt useful for applications to optoelectronic structures such as vertical-cavity surface-emitting lasers (VCSEI) [1,2]. Distributed Bragg mirror structures prepared with this material system for 1.3-1.5 µm wavelength VCSEL devices are generally developed on InP substrates [3].…”
Section: Introductionmentioning
confidence: 99%
“…Since the seminal works of Gibbs in the late 1970s, 1 considerable efforts were devoted to the development and optimization of one-dimensional ͑1D͒ semiconductor microcavities for bistable operation. 2 Further field confinement and a high versatility to control light propagation can be achieved using two-dimensional photonic crystals ͑2DPCs͒. Indeed, modern design of 2DPCs allows high quality ͑Q͒ factors that dramatically reduce bistability thresholds, which are known to scale as Q −2 .…”
mentioning
confidence: 99%
“…A previous experimental study has confirmed the advantage to have only one V-group element system to precisely control the Bragg stack composition and periodicity and to use also interface refinements to decrease the series resistance (3,4). This work has also led to the demonstration of an optically pumped VCSEL showing excellent quality mirrors (3).…”
Section: Introductionmentioning
confidence: 69%